2022
DOI: 10.3390/jcm11061539
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Heart Rate Responses to an Isokinetic Testing Protocol in Professional Soccer Players

Abstract: The aim of this study was to determine blood pressure (BP) and heart rate (HR) responses triggered during an isokinetic testing protocol in professional soccer players and compare cardiovascular parameters at completion of this isokinetic protocol with those during a treadmill test. Using purposive sampling, 63 professional soccer players were recruited. Cardiovascular responses were measured noninvasively during a bilateral testing protocol of knee flexion and extension. Treadmill ergospirometry following an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…The finding that vital capacity improved more significantly in the KRTG compared to both the CG and the BWRTG suggests that KRTG may have a more pronounced effect on lung function, possibly due to the involvement of both aerobic and anaerobic components in kettlebell exercises [ 58 ]. The observed reductions in resting heart rate and respiratory rate in both the BWRTG and KRTG are consistent with previous studies, which have reported that regular exercise can lower resting heart rate, reflecting increased cardiac efficiency, and reduce respiratory rate, indicating more efficient oxygen utilization [ 59 , 60 ]. These improvements contribute to a reduced risk of cardiovascular diseases and better overall health [ 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…The finding that vital capacity improved more significantly in the KRTG compared to both the CG and the BWRTG suggests that KRTG may have a more pronounced effect on lung function, possibly due to the involvement of both aerobic and anaerobic components in kettlebell exercises [ 58 ]. The observed reductions in resting heart rate and respiratory rate in both the BWRTG and KRTG are consistent with previous studies, which have reported that regular exercise can lower resting heart rate, reflecting increased cardiac efficiency, and reduce respiratory rate, indicating more efficient oxygen utilization [ 59 , 60 ]. These improvements contribute to a reduced risk of cardiovascular diseases and better overall health [ 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…Other similar works are presented in [28,29]. The work [30] describes the blood pressure and heart rate responses triggered by an isokinetic testing protocol in professional soccer players and compares cardiovascular parameters at the completion of the isokinetic protocol with those during a treadmill test.…”
Section: Introductionmentioning
confidence: 99%